Filling the gaps in a highly diverse Neotropical lizard lineage: a new and endemic genus of Cercosaurinae (Squamata: Gymnophthalmidae) with the description of two new species from the Northern Andes of Colombia. Issue 5 (3rd July 2020) - Fang, José M.; Vásquez-Restrepo, Juan D.; Daza, Juan M.
Abstract : In the last decade, understanding of the Neotropical lizards family Gymnophthalmidae has changed dramatically with the recognition of several new genera, resolution of non-monophyly, definition of previously unknown lineages and refined biogeographic hypotheses. Recent field explorations on the northern Cordillera Central in Colombia uncovered two undescribed species that cannot be assigned to any currently recognized gymnophthalmid genus. Based on a molecular phylogenetic analysis combined with morphological and genetic distances, we describe a new genus and two new species from the northern Andes of Colombia. Magdalenasaura gen. nov. is restricted to the Magdalena biogeographic province and is sister to the cis-Andean genus Gelanesaurus . The new genus can be readily distinguished from all other Cercosaurinae genera by a combination of genetic and morphological characters. The new genus contains Magdalenasaura leurosquama sp. nov. and M. adercum sp. nov., both found in forested habitats near streams at altitudes ranging from 1300 to 1850 m on the eastern flank of the northern Cordillera Central in Colombia. We differentiate the Cercosaurinae genera from Colombia based on general scutellation. Filling the gaps of the tremendous diversity of gymnophthalmid lizards will improve taxonomic and biogeographic hypotheses to better understand the evolution of endemic lineages from the north-western corner of South America. http://zoobank.org/urn:lsid:zoobank.org:pub:47E621FD-BEA9-4C65-87D8-D832C4EEC3A4